SOCIAL INEQUALITY AND ACCESS TO EDUCATION: A LITERATURE REVIEW ON THE IMPACT OF SOCIAL STRATIFICATION ON EDUCATION IN DEVELOPING COUNTRIES - Hikmat (GoAcademica CRP, 2024)
Educational inequality remains a persistent challenge in many developing countries, where social stratification significantly shapes access to learning opportunities. This literature review examines the relationship between social inequality and educational access, with particular attention to socioeconomic status, gender, cultural background, and geographical disparities. Using an integrative approach, this study synthesizes findings from peer-reviewed articles, reports from international organizations, and theoretical contributions in the sociology of education. The review identifies five recurring themes: (1) the impact of family socioeconomic status on school participation and attainment; (2) gender disparities that reflect broader cultural and structural biases; (3) the urban–rural divide in terms of resources and institutional quality; (4) the role of state policies and global frameworks, such as the Sustainable Development Goals, in mitigating inequalities; and (5) the implications of social stratification for long-term social mobility. The analysis highlights that while education is often perceived as a pathway to equal opportunity, in practice it frequently reproduces existing social hierarchies. The review concludes by stressing the importance of affirmative policies, digital inclusion, and community-based interventions to reduce educational disparities. It also suggests future research directions, particularly in the context of post-pandemic transformations and the growing role of technology in bridging inequality.